Варяг - Мазин Александр Владимирович (Варяжская Русь, 2022)
Экземпляры: ф.22 (20240522) / Инвентарный номер: 64751 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 13 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-442